Pertumbuhan Penjualan dan Kinerja Keuangan Perusahaan: Peran Moderasi Pengawasan Komisaris Independen - Devianty Kumalasari; Nadia Angelia; Yulius Jogi Christiawan (Business Accounting Review, 2021)
Growth maximization theory explains that the different goals of agents and principals can be equated by maximizing sales growth. On the other hand, agency theory explains that agents must be supervised to act in accordance with the wishes of the principal. Independent commissioners are able to assist principals in supervising the performance of agents. Based on these two theories, this study aims to prove whether the supervision of independent commissioners will influence the relationship between sales growth and financial performance. The study was conducted on 66 manufacturing companies listed on the Indonesian Stock Exchange (IDX) for 2018-2020. This research uses the multiple linear regression techniques of panel data. The study results prove that the higher the sales growth and independent commissioner supervision, the higher the financial performance. Furthermore, it is proven that in companies with high independent commissioner supervision, the increase in financial performance caused by sales growth was more significant than in companies with low independent commissioner supervision. The results of this study are expected to be used by shareholders of growing companies to maximize the supervisory role of independent commissioners and investors to predict the company's financial performance.